2016
DOI: 10.5498/wjp.v6.i4.449
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioural therapy for obsessive-compulsive disorder co-occurring with psychosis: Systematic review of evidence

Abstract: AIMTo review available evidence on the use of cognitive behavioural therapy (CBT) for treating obsessive compulsive disorder co-occurring with psychosis.METHODSIn this paper we present a detailed and comprehensive review of the current literature focusing on CBT treatment of obsessive compulsive disorder (OCD) co-occurring with schizophrenia or schizoaffective disorder. We identified relevant literature published between 2001 and May 2016 through MEDLINE/PubMed search using as search string (“obsessive compuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Despite the Pavlovian school's extensive research on autonomic conditioning (Gantt, 1964), the role of Pavlovian conditioning of the ANS in the regulation of OT and related hormones in autonomic learning has received relatively little attention over the past 50 years. While Pavlovian conditioning is used to illicit a fear response in animal research, these papers are almost exclusively focused on brain memory (Stockhorst & Antov, 2015), central nervous system theories (Izquierdo, Furini, & Myskiw, 2016), and operant conditioning to overcome the effects (Tundo & Necci, 2016). The exclusive focus on brain-based mechanisms has obscured a whole-organism view of mammalian biology, one that takes into account the important role of the ANS, especially in the regulation of emotional behavior through bi-directional signaling between the viscera and the brain stem via the vagus nerve.…”
Section: Visceral Signalling and Emotional Behaviormentioning
confidence: 99%
“…Despite the Pavlovian school's extensive research on autonomic conditioning (Gantt, 1964), the role of Pavlovian conditioning of the ANS in the regulation of OT and related hormones in autonomic learning has received relatively little attention over the past 50 years. While Pavlovian conditioning is used to illicit a fear response in animal research, these papers are almost exclusively focused on brain memory (Stockhorst & Antov, 2015), central nervous system theories (Izquierdo, Furini, & Myskiw, 2016), and operant conditioning to overcome the effects (Tundo & Necci, 2016). The exclusive focus on brain-based mechanisms has obscured a whole-organism view of mammalian biology, one that takes into account the important role of the ANS, especially in the regulation of emotional behavior through bi-directional signaling between the viscera and the brain stem via the vagus nerve.…”
Section: Visceral Signalling and Emotional Behaviormentioning
confidence: 99%
“…Flygare and colleagues64 found that OCD patients with ASD received less benefit from CBT with ERP than those without ASD potentially due to greater difficulties engaging and adhering to exposure-based treatment. While difficulty treating OCD in the presence of other serious mental illnesses (eg, psychotic disorders) is often noted clinically, a small number of case studies suggest that ERP is not iatrogenic for these populations 65…”
Section: Predictors and Moderators Of Erp Treatment Outcomementioning
confidence: 99%
“…Treatment of SGA-induced OCS/OCD involves reduction of antipsychotic dose (e.g., reduction of dose of clozapine if feasible), change to another antipsychotic with minimal influence on serotonergic systems such as aripiprazole, amisulpride, or haloperidol,[55] addition of aripiprazole,[73] and addition of SSRI[69] and CBT. [74]…”
Section: Management Of Obsessive–compulsive Symptoms/obsessive–compulmentioning
confidence: 99%